Long-term partners – Reflections on the shifts in partnership responses to domestic violence - Welsh, Kirsty (International review of victimology, 2023)
Whilst pioneering partnership work first took place in the battered women’s or refuge movement in England and Wales, the response that came to dominate in the 1990s and 2000s mirrored that associated with crime prevention more generally and Home Office crime prevention in particular. This reflected the increasing positioning of domestic violence as ‘real crime’ and the moves at this time to view domestic violence through a ‘crime lens’. In the last 10 years or so, there has been a clear shift, with the prevailing approach now dominated by initiatives such as Multi-Agency Risk Assessment Conferences, Independent Domestic Violence Advisors and Specialist Domestic Violence Courts. These initiatives have achieved considerable success in reducing risks to high-risk victims. Yet, in doing so, they establish a very particular framework for responding to domestic violence, positioning and promoting it as high-risk victimisation and moving to see it through an ‘exceptional risk’ lens. This paper examines shifts in the partnership response to domestic violence in England and Wales. It argues that, not only are the vast majority of lower risk women excluded from the prevailing framework but, in focusing on high-risk reduction, intervention within this framework fails to address women’s complicated and often contradictory needs in relation to abuse. The prevailing partnership response rests on a notion of safety as risk cessation rather than one which prioritises expansion of women’s space for action and freedom from the legacies of abuse. It concludes that, whilst partnership has huge practical and philosophical potential as a response to domestic violence, only by seeing domestic violence through the lens of diminished possibilities and with a broader conceptualisation of safety can a partnership framework support women to achieve theirs.